IMPLEMENTASI E-COURT DALAM ASAS PERADILAN SEDERHANA, CEPAT DAN BIAYA MURAH DI PENGADILAN AGAMA JOMBANG: Implementasi E-Court Dalam Asas Peradilan Sederhana, Cepat Dan Biaya Murah Di Pengadilan Agama Jombang - Sapri Ali; Achmad Asfi Burhanudin; Furotul Khasanah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This research aims to analyze the implementation of E-Court in supporting the principles of simple, fast, and low cost justice at the Jombang Religious Court. The E-Court system was present as a form of innovation of the Supreme Court in responding to the challenges of the times and the need for modernization of the judicial system. This research used descriptive qualitative approach with data collection techniques through interview, observation, and documentation study. The results showed that E-Court provides efficiency in administrative and judicial processes, although there are still some obstacles such as limited digital literacy among the justice-seeking community. In conclusion, E-Court supports the principles of simple, fast, and low cost justice, but still requires optimization in terms of implementation and infrastructure support. Keywords: E-Court, judicial principles, simple, fast, low cost, Religious Court